Studies on seagrasses of North Sulawesi, Indonesia and adjacent waters: A critical review - Wagey, Billy T. (Universitas Sam Ratulangi, 2018)
The importance of seagrasses in terms of ecological and economic benefits are well-known. This paper describes the status of research on seagrasses conducted so far, with relevance to the North Sulawesi region. Most of the studies done in Indonesia, especially in North Sulawesi, have focused on species richness and biodiversity as well as basic biological questions such as biomass and morphometric differences of certain seagrass species between sampling localities. While several studies have been conducted, there is a general need for Indonesian marine scientists to expand research areas related to food-web dynamics and inter-connectivity of major fishery and nursery habitats (mangroves-seagrass-coral reefs) with the aid of modern tools (e.g. molecular approach).Â Â Â Keywords: benefits, biology, ecology, economic, seagrass